Eradication of Helicobacter pylori with triple therapy regimen (omeprazole, clarithromycin and amoxicillin) in children for seven days (A Pilot Study) - Mehri Najafi; Fariba Seighali (Mazandaran University of Medical Sciences, 2014)
Background and purpose: Successful treatment of Helicobacter pylori infection causes not only eradication of pathogen, but also prevents the associated diseases such as peptic ulcer, gastric carcinoma and lymphoma. The aim of this study was to evaluate the efficacy of 7 days triple therapy as a lowest drug resistance, shortest duration and fewer numbers of drugs in children. Materials and Method: The target population was 22 children <15 years with peptic disease complaints. The inclusion criteria were: positive endoscopic finding, inflammatory evidence in gastric biopsy and presence of Helicobacter pylori in gastric mucosa. Two pieces from incisura and body of gastric mucosa were taken and stained with Gimsa. Helicobacter pylori positive patients were treated with omeprazol, clarithromycin and amoxicillin for 7 days. One month later, all cases were evaluated by repeated endoscopy or Urea Breath Test and H pylori eradication were assessed. Data was gathered and analyzed with SPSS software, and McNamara's and Chi-Square test were performed. Results: Nineteen patients were studied including twelve boys, 26.3% 2-6 years and the rest older than 6 years. The most common clinical presentations and endoscopic findings were chronic abdominal pain (74%) and nodularity (47.4%), respectively. The per-protocol and intention-to-treat H. pylori eradication rates were 84.2% and 76%, respectively in seven days triple therapy regimen. Conclusion: Seven days triple therapy successfully eradicated H pylori in children.